The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/jcp.28147
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of vacuolar H+‐ATPase subunits by transforming growth factor‐β1 in salivary ducts

Abstract: Bicarbonate concentration in saliva is controlled by the action of acid–base transporters in salivary duct cells. We show for the first time expression of ATP6V1B1 in submandibular gland and introduce transforming growth factor‐beta (TGF‐β) as a novel regulator of V‐ATPase subunits. Using QRT‐PCR, immunoblotting, biotinylation of surface proteins, immunofluorescence, chromatin immunoprecipitation, and intracellular H(+) recording with H(+)‐sensitive dye 2′,7′‐bis‐(carboxyethyl)‐5‐(and‐6)‐carboxyfluorescein we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…During CNS development—although both TGF-β2 and TGF-β3 isoforms are expressed in neural progenitor cells, in radial glia cells and in differentiating neurons—TGF-β2 has been considered relatively more relevant compared to TGF-β3 [ 28 ]. Interestingly, several transport proteins have been identified as targets of TGF-β signaling within and outside the CNS, including CFTR, ENaC, distinct V-ATPase subunits in epithelia and NBCe1 in astrocytes [ 29 , 30 , 31 , 32 ]. We have previously shown that TGF-β signaling regulates trafficking of KCC2 to the plasma membrane in differentiating and mature mouse hippocampal neurons via TGF-β/CREB/Rab11b pathway [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…During CNS development—although both TGF-β2 and TGF-β3 isoforms are expressed in neural progenitor cells, in radial glia cells and in differentiating neurons—TGF-β2 has been considered relatively more relevant compared to TGF-β3 [ 28 ]. Interestingly, several transport proteins have been identified as targets of TGF-β signaling within and outside the CNS, including CFTR, ENaC, distinct V-ATPase subunits in epithelia and NBCe1 in astrocytes [ 29 , 30 , 31 , 32 ]. We have previously shown that TGF-β signaling regulates trafficking of KCC2 to the plasma membrane in differentiating and mature mouse hippocampal neurons via TGF-β/CREB/Rab11b pathway [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cAMP pathway-elicited β3-AR stimulation might activate CREB signaling and transcription. Indeed, Kluge et al (2019) described CREB binding sequences in the promoter regions of the human B1 subunit of the V1 domain of H + -ATPase (ATP6V1B1) in the human submandibular cell line. This aspect deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%